Expanded Endoscopic Endonasal Treatment of Primary Intracranial Tumors within the Paranasal Sinuses. (13th August 2013) - Ali, Zarina S.; Lang, Shih-Shan; Adappa, Nithin D.; Barkley, Ariana; Palmer, James N.; Lee, John Y. K.
Abstract : Objective . Meningiomas and schwannomas represent a subset of primary intracranial tumors that are rarely identified exclusively in the paranasal sinuses. Here, we describe our experience with minimally invasive endoscopic endonasal approaches for the treatment of these tumors. Methods . We retrospectively reviewed the clinical, surgical, and radiographic characteristics of adults with pathologically confirmed sinonasal meningiomas and schwannomas located within the paranasal sinuses that were resected via an expanded endoscopic endonasal approach. Results . Five patients (1 male, 4 females) underwent an endoscopic endonasal approach for resection of sinonasal tumor. Clinical symptomatology most commonly included nasal obstruction, in addition to headache, jaw pain, anosmia, and chronic rhinosinusitis. Tumors were located exclusively within the sinonasal cavity and were on average 2.2 cm (range 1.4–3.8 cm). Pathology revealed 2 cases of meningioma and 3 cases of schwannoma. No evidence of tumor recurrence occurred over average followup of 1.5 years (range 0.11–3.9 years). Conclusion . Our case series suggests that an expanded endoscopic endonasal approach with a combined neurosurgical-otorhinolaryngologic team for the resection of sinonasal meningiomas and schwannomas offers an effective treatment option. Further studies that include a larger number of patients over a longer follow-up period are required to compare outcomes between minimally invasive and open approaches.